Evolutionary Game Analysis of Quality and Safety Regulatory Mechanism In Agricultural E-Commerce Supply Chain Considering Government Subsidy - Zhou, Linan; Zheng, Jianzhuang; Shu, Yingying; Li, Hangying (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The quality and safety of agricultural products on e-commerce platforms are increasingly of increasing concern in China. This study constructs a three-party evolutionary game model to analyze the production decisions of producers and the regulatory decisions of e-commerce platforms. It explores the influence of online social supervision and the government's subsidy policy. The results show that social supervision helps to externally discourage producers from colluding with e-commerce platforms to produce 'fake' green agricultural products. On this basis, a reasonable subsidy policy in addition to the existing punitive measures can internally motivate producers and e-commerce platforms to consciously produce and sell green agricultural products in a compliant manner, thus realizing a win-win situation and a collaborative environment for all three parties. Moreover, the government should construct a long-term subsidy mechanism for e-commerce platforms and a short-term subsidy mechanism for producers, so as to guarantee the sustainable development of the green agricultural e-commerce supply chain.